Verbal vs Non-Verbal Means of Expressing Emotion in CMC - Kirakosyan, Tatevik (Armenian Folia Anglistika, 2013)
Emotions have a unique place in a person’s life. They are reflected in each human activity and are expressed in language and through language not only during face-to-face, but also online communication. The article pays special attention to the expressions of emotions in these two fields of communication taking into consideration the verbal and non-verbal peculiarities of the expression of emotions.